(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
The study of Latin has deep roots in medical education and remains an integral part of learning the scientific terminology, nomenclature, and fundamentals of modern medicine. Although the teaching of Latin has declined in recent decades, the continued importance and benefits of teaching Latin to health science students is increasingly recognized among medical education leaders. This article outlines some key principles for the effective recovery and teaching of Latin in medical schools and allied health programs.